1999
DOI: 10.1080/014311699211660
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between radar backscatter and accumulation rates on the Greenland ice sheet

Abstract: C-band radar backscatter generally seems to be inversely related to accumulation rate across Greenland's dry snow zone. A coupled snow metamorphosis± backscatter model was constructed in order to investigate the observation. Accumulation rate and mean annual temperature were the coupled-model inputs. In a local area where accumulation rate is known very accurately the model predicts the backscatter level along several transects within the calibration uncertainties of the ERS-1 SAR data. The analysis was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 19 publications
3
47
2
Order By: Relevance
“…As observed earlier by Antarctic and Greenland ice sheet studies [3], [8], [11], [23], [30], [54], such changes are mirrored by the corresponding backscattering signatures, which show a clear rise in with decreasing snow accumulation. Larger grain sizes and a higher number of strata per depth unit are thought to cause an increased volume scattering, accompanied with a reduction of penetration depth.…”
Section: A Transect Neumayer-kottassupporting
confidence: 50%
See 3 more Smart Citations
“…As observed earlier by Antarctic and Greenland ice sheet studies [3], [8], [11], [23], [30], [54], such changes are mirrored by the corresponding backscattering signatures, which show a clear rise in with decreasing snow accumulation. Larger grain sizes and a higher number of strata per depth unit are thought to cause an increased volume scattering, accompanied with a reduction of penetration depth.…”
Section: A Transect Neumayer-kottassupporting
confidence: 50%
“…This assumption is confirmed by traverse studies [45] that found the number of strata within the upper 2 m to reach up to 60, with an average of 35. These findings compare with observations from central Greenland, where increased backscattering was also associated with intensified layering together with increased grain sizes due to low accumulation rates [11], [23]. Class I and II cluster means are not very distinct for Nscat and thus could not be correctly discriminated on the plateau area.…”
Section: B Snow Pack Classificationcontrasting
confidence: 49%
See 2 more Smart Citations
“…In active mode, a different method to derive accumulation based on the difference between backscattering coefficients at various incidence angles was developed for Greenland (Drinkwater et al, 2001;Forster et al, 1999).…”
Section: Application 3: Net Accumulationmentioning
confidence: 99%